Papillary Thyroid Micro Carcinoma: The Incidence of High-Risk Features and Its Prognostic Implications - Gao, Rui; Jia, Xi; Liang, Yiqian; Fan, Kun; Wang, Xiaoxiao; Wang, Yuanbo; Yang, Lulu; Yang, Aimin; Zhang, Guangjian (Frontiers in Endocrinology, 2019)
Background: The current trend in management of papillary thyroid micro carcinoma (PTMC) has become more conservative. However, prevalence of high-risk characteristics that can only be revealed post-surgery existed. Patients and clinicians need to estimate the risks and understand the prognostic meaning of these factors. Methods: We retrospectively analyzed 246 consecutive patients with PTMC who underwent surgery at our institution between 2015 and 2017. Clinical and histopathological parameters that may indicate recurrent disease were investigated. The responses to therapy in cases of different risks of recurrence were analyzed. Results: A total of 79.26% (195/246) of patients received total thyroidectomy (TT), of whom 177 (90.77%) also received central node neck dissection. Radioiodine ablation (RAI) was applied in 64.23% (158/246) of the cohort of patients. Intermediate-risk features were identified in 27.64% (68/246) after primary treatment. After a median follow-up of 18 months (range, 6–39 months), 121 of 158 (76.58%) patients who received TT+RAI were evaluated as an excellent response. An incomplete response (IR) was observed in 14.56% (23/158) of this group of PTMC. Multivariate analysis identified extra thyroid extension (P=0.001) and intermediate-high risk stratification (P=0.014) as significant and independent risk factors for an IR. Conclusions: A total of 27.64% of PTMC cases evaluated as a low risk of recurrence pre-surgery show intermediate to high-risk disease post-surgery, and this leads to a higher rate of IR.